Monsoon effects on the residence time of a coastal lagoon in southwestern Taiwan. (5th February 2020) - Lee, Hung-Jen; Meng, Pei-Jie; Chen, Chung-Chi; Tew, Kwee Siong
Abstract: A three-dimensional, high-resolution numerical model with tide-generating and wind forces was used to simulate a passive tracer to study the water mass flushing rate in a coastal lagoon— Tapeng Bay. Model results show that north–northwesterly monsoons in winter can suppress ebb tidal currents flowing northwestward and concurrently suppress lagoon water exchanges with open shelf water, leading to a poor flushing rate. By contrast, both the westerly and southeasterly prevailing wind conditions in summer allowed lagoon water to mix, producing long-distance motion in the form of tidal residual currents from the southeast toward the northwest of the bay. This wind stress disturbance induced a horizontal mixing of the longitudinal lagoon water and led to greater water mass exchanges between Tapeng Bay and the open shelf. Therefore, tide-generating forces and suitable monsoons crucially influence the residence time of water mass in coastal lagoons. Highlights: For more accurately assess water exchange in Tapeng Bay, a high-resolution numerical model is used to simulate the water residence time under different Asian monsoon conditions; it is verified. The observations, including CTD and ADCPs sampling, usefully help the study. The model results suggest that it is not appropriate to use a box model to estimate residence times for coastal lagoons worldwide, particularly where the lagoons are not well-mixed water.